ANALISIS POTENSI POLITIK UANG DALAM PEMILIHAN KEPALA DESA - Mahyudin Mahyudin; Andre Putra Yudarsat; Rustam Muhusi (Program Studi Ilmu Pemerintahan, Universitas Muhammadiyah Buton, 2022)
The purpose of this research is to assess the potential of money politics in the Liya Mawi Village Head Election, Wakatobi Regency. This study employs descriptive analysis with a quantitative approach, a research technique used to investigate the status of natural things in which the researcher serves as the primary instrument. According to the findings of this study, in terms of factors influencing community participation in the 2021 Liya Mawi Village Head election, the average respondent who chose yes for the three questions related to the element of community involvement in the 2021 Village Head election was 51 (51.33 percent), while the average respondent who chose no was 49 or less (48.66 percent). As a result, it has a 51 percent influence on the participation of Liya Mawi Village people in the 2021 Village Head election. This is demonstrated by the number of respondents from the three question indicators who opted to answer Yes by 51 (51.33 percent) and No by 49 (48.66 percent). While the form of voter behavior in the Liya Mawi village head election in 2021, the Liya Mawi Village community has a perception of money politics, with 42 respondents accepting money for rational reasons, 31 respondents accepting money for sociological reasons, and those receiving money for social reasons. psychology of politics There were 27 responses. Thus, according to the three indicators, people who got enormous quantities of money in Liya Mawi Village during the 2021 Village Head election were chosen based on logical criteria, namely 42 respondents.